Factors affecting employe performance at the central bank of the Republic Indonesia: Submit Jurnal - Ade Jamaludin (Institute of Computer Science (IOCS), 2023)
This study aims to analyze factors that can improve employee performance with work discipline and organizational citizenship behavior as mediating variables at the Central Bank of the Republic of Indonesia, Banten Province. Given the importance of implementing motivation and job satisfaction for companies to further improve employee performance at the Central Bank of the Republic of Indonesia. The research method uses a quantitative approach using 152 saturated samples of employees of the Central Bank of the Republic of Indonesia, Banten Province, which were collected through questionnaires and data analysis using the SmartPLS 3.2.9 program. The results of the study show that work motivation and job satisfaction have a positive and significant effect on employee performance both directly and mediated by work discipline and organizational citizenship behavior. Contributions to this research can be used for academic purposes and practical purposes which can be used as a guide for the leadership of the Central Bank of the Republic of Indonesia.